2016
DOI: 10.1136/injuryprev-2015-041828
|View full text |Cite
|
Sign up to set email alerts
|

Poison prevention practices and medically attended poisoning in young children: multicentre case–control study

Abstract: IntroductionChildhood poisonings are common, placing a substantial burden on health services. Case–control studies have found inconsistent evidence about modifiable risk factors for poisonings among children aged 0–4 years. This study quantifies associations between poison prevention practices and medically attended poisonings in children aged 0–4 years.MethodsMulticentre case–control study conducted at hospitals, minor injury units and family practices from four study centres in England between 2010 and 2013.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 34 publications
1
23
0
3
Order By: Relevance
“…Reducing the poisoning rate among Aboriginal children requires combined strategies of household storage interventions, accessible poisons information centres and enforcement of packaging legislation 43. No known injury prevention programmes have specifically addressed unintentional poisoning in Aboriginal communities44; however, safe storage of medications is known to be key to childhood poisoning prevention 15. Aboriginal families and low-income families may face barriers in promoting safe storage due to costs of safety equipment and prohibitions on home installations in public housing or rental properties 45 46.…”
Section: Discussionmentioning
confidence: 99%
“…Reducing the poisoning rate among Aboriginal children requires combined strategies of household storage interventions, accessible poisons information centres and enforcement of packaging legislation 43. No known injury prevention programmes have specifically addressed unintentional poisoning in Aboriginal communities44; however, safe storage of medications is known to be key to childhood poisoning prevention 15. Aboriginal families and low-income families may face barriers in promoting safe storage due to costs of safety equipment and prohibitions on home installations in public housing or rental properties 45 46.…”
Section: Discussionmentioning
confidence: 99%
“…Unsafe storage of medicines and household chemicals [ 6 ], low parental education, low socioeconomic status, larger family size (≥4 children), and history of previous poisoning are previously reported risk factors for acute unintentional childhood poisoning [ 7 , 8 ]. A recent study concluded that poor child-caregiver relationship is an important risk factor for unintentional poisoning [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Storing cabinets or drawers within a child's reach should be locked or secured with a childproof lock. A UK study (6) showed that parents of children who had a poisoning incident more often did not store medicines out of children's reach or put away medicines or household products after use than control parents.…”
Section: Resultsmentioning
confidence: 99%